Executive-legislature relations in Nigeria’s emerging presidential democracy (2005)
This paper investigates the recurrent executive-legislature face offs in Nigeria in the Fourth Republic. It examines the underlining issues and strategies adopted by each arm in pursuit of its interests and how these strategies fuel and intensify the conflicts, noting the opportunities and challenges for reducing the tendency towards government immobilism. It argues that three factors have been critical to the relentless acrimony between the legislature and the executive. The first is the relative underdevelopment of the legislature in terms of institutional processes, role perception and rules of conduct. The second is the incoherence of the ruling People's Democratic Party (PDP) that rendered it incapable of enforcing discipline among its members in government. The third is the hangover from militarism, which reflects in the strategies adopted by both parties.